2015
DOI: 10.2174/1874350120150601e001
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Feeling of Security: A Candidate for Assessing Remission in Borderline Patients ?

Abstract: Abstract:The aim of the study was for the first time to examine whether adults diagnosed with Borderline Personality Disorder feel that their sense of security improved through treatment with Dialectical Behavioral Therapy conducted one or two years earlier. In the current study perceived security was defined as a feeling of being free of worrisome or threatening phenomena. Twenty-three patients (2 men and 21 women) aged 18 to 57 years, were recruited from five teams in Southwest Sweden. A questionnaire was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Some people perceive themselves as healthy despite suffering from one or more chronic diseases, while others perceive themselves as ill, when no objective evidence of disease can be found. Nowicki and co-workers (Nowicki et al 2018) suggested that the perception of health was a personal value. In 1946, the World Health Organization defined health as a state of complete physical, mental, and social well-being, and not merely the absence of disease or infirmity.…”
Section: Human Values and Subjective General Health (Sgh)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some people perceive themselves as healthy despite suffering from one or more chronic diseases, while others perceive themselves as ill, when no objective evidence of disease can be found. Nowicki and co-workers (Nowicki et al 2018) suggested that the perception of health was a personal value. In 1946, the World Health Organization defined health as a state of complete physical, mental, and social well-being, and not merely the absence of disease or infirmity.…”
Section: Human Values and Subjective General Health (Sgh)mentioning
confidence: 99%
“…The Eurobarometer (2012) survey revealed that health leads the list of values associated with happiness in all European member states assessed except Denmark, where respondents first mention love. Several studies relate SGH with the human values of Stimulation (e.g., Sagiv and Schwartz 2000), Hedonism (e.g., Pino-Domínguez et al 2016), Achievement (e.g., Minkkinen et al 2017), Power (e.g., Verstraete et al 2018), Security (e.g., Norlander et al 2015), Conformity (e.g., del Pilar Sánchez-López et al 2014), Tradition (e.g., Baiocchi-Wagner andOlson 2016), Benevolence (e.g., Bevan and Sparks 2014), and Universalism (e.g., Hughes 2017).…”
Section: Human Values and Subjective General Health (Sgh)mentioning
confidence: 99%